Factor H-related 1 and heparan sulfate architecture contribute to complement dysregulation in C3 glomerulopathy - Slagle, Amanda K.; Ghiringhelli Borsa, Nicolo; Wang, Kai; Taylor, Amanda O.; Meyer, Nicole C.; Jones, Michael B.; Walls, William D.; Nelson, Angela F. M.; Roberts, Sarah M.; Sun, Mingyao; Goicoechea de Jorge, Elena; Rodriguez de Cordoba, Santiago; et al. (Frontiers in Immunology, 2025)
IntroductionDysregulation of the alternative pathway of complement underlies the pathogenesis of C3 glomerulopathy (C3G). Because Factor H (FH) prevents excessive alternative pathway activity while Factor H-related protein 1 (FHR-1) is believed to enhance this response, we investigated the balance between FH and FHR-1 in C3G.MethodsTo assess the role of FHR-1 in C3G pathogenicity, we used a multiplex ligation-dependent probe amplification to detect copy number variants in CFHR3-CFHR1 and enzyme linked immunosorbent assays to measure circulating protein levels in C3G patients compared to controls. Additionally, an in vitro C3b deposition assay was used to characterize the functional impact of FHR-1 on local complement activity.ResultsIn this study, we confirm that CFHR3-CFHR1 copy number impacts C3G risk. In C3G patients with two copies of CFHR3-CFHR1, the FHR-1:FH protein ratios are increased compared to controls; however, this increase is not disease specific. Rather, it is reflective of deteriorating renal function and was also observed in a second cohort of patients with chronic kidney disease from a variety of other causes. Functional studies showed that FHR-1 competes with FH to increase C3b deposition on mouse mesangial cell surfaces, an effect enhanced by heparan sulfate cleavage.DiscussionAltogether, we show that as renal function declines, a change in the FHR-1:FH ratio combined with changes in heparan sulfate architecture increase complement activity. These findings suggest that complement activity may contribute to the chronic inflammation and progression of renal damage associated with chronic kidney disease.